Comparing Telephone Counseling With Reminding to Promote On-Time Repeated Mammography: A Randomized Trial in a Cohort With 4 Years Follow-Up. (February 2020) - Costanza, Mary E.; Luckmann, Roger; Frisard, Christine; White, Mary Jo; Cranos, Caroline
Background. Long-term continuous adherence to biennial screening mammograms as guidelines recommend remains low. Limited evidence suggests that reminder calls may increase short-term adherence as much as telephone counseling, but research is needed comparing the long-term effects of these two approaches. Purpose. To compare the impacts of two telephone outreach interventions and mailed reminders on 4-year continuous mammography adherence. Method. A cohort of 3, 215 women, age 50 to 81 years, was selected from 30, 160 women from a 4-year randomized trial of three interventions to promote biennial mammography: reminder letter only (LO), letter plus reminder call (RC), and two letters plus educational material and a counseling call (CC). Women selected remained eligible for the trial all 4 years and received annual interventions as needed. The proportion with a mammogram in the last 24 months was determined at baseline and four annual time points. Results. Continuous adherence at all four time points was higher in the RC (78.8%) and CC arms (78.8%) than in the LO arm (75.1%; p < .001). Multivariable analysis confirmed this finding: CC (odds ratio = 1.27; 95% confidence interval = [1.01, 1.61]) and RC (odds ratio = 1.23; 95% confidence interval = [0.98, 1.56]). Only 27.8% of women eligible for an initial counseling call actually received counseling. Conclusions. Compared with letters alone, outreach calls can modestly increase continuous mammography adherence among insured women with consistent primary care. Telephone counseling was no more effective than a reminder call, possibly due to limited acceptance of counseling calls by women who may find them unwelcome or unnecessary.